Volar Locking Plate versus Closed Reduction and Immobilization for Distal Radius Fracture in the Elderly: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Latypov, Niyaz; Golubev, Igor; Borisova, Alyona (Journal of Wrist Surgery, 2023)
Introduction A systematic review and meta-analysis of randomized controlled trials was conducted to compare surgical treatment using open reduction and internal fixation (ORIF) with volar locking plates (VLP) to conservative treatment with closed reduction and immobilization in elderly patients aged ≥60 years with acute displaced distal radius fractures.Methods A search of the MEDLINE, Scopus, and Central Register of Controlled Trials (CENTRAL) databases was conducted. Clinical and radiographic measures at 12 months were compared between groups by pooling the mean difference. The complication rates were compared by pooling relative risk ratios. Pooled mean differences of Disabilities of the Arm, Shoulder, and Hand (DASH) and Patient-Rated Wrist Evaluation (PRWE) results were compared with the published minimal clinically important difference (MCID) to evaluate the clinical relevance of the results.Results The initial search yielded 766 records, from which 6 articles were selected for the final analysis. The results of the DASH questionnaire at 12 months of follow-up were significantly lower in the surgical treatment group with a mean difference (MD) of –3.61 points (95% confidence interval [CI]: –6.48 to –0.73). No statistically significant difference was found in the PRWE questionnaire (MD = –3.14 points [95% CI: –7.32 to 1.04]). Radiological results were significantly better in the surgical treatment group and no significant difference in the overall complication rate between the groups was detected. Found MD for DASH and PRWE did not reach the published MCIDs.Conclusion This study suggests that for elderly patients aged ≥60 years with acute displaced distal radius fractures, surgical treatment using ORIF with VLP does not provide clinically relevant benefits compared with conservative treatment with closed reduction and immobilization at the 12-month follow-up, despite demonstrating better radiological results.
Keywords: distal radius fracture; elderly; volar locking plate; cast; immobilization